PENYELESAIAN PEMUTUSAN HUBUNGAN KERJA KARENA KESALAHAN BERAT PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 012/PUU-I/2004 (Lex Jurnalica, 2016)
AbstractWhen workers committing a crime in the workplace as the provisions of Article 158 of Labour Law No. 13/2003, then with certain requirements (proof: the workers / laborers caught in the act, no recognition or supported by at least two witnesses) employers can dismiss workers unilaterally, without going through the Industrial Relations Court determination procedures. The Constitutional Court (MK) Decision Number 012 / PUU-I / 2003 has stated that Article 158 of the Labor Law, the Law does not have binding force because it is considered contrary to Article 27 paragraph (1) of the Constitution of 1945. Following the Ruling of the Constitutional Court, Employers can not layoffs before the court ruling general and binding (inkracht). Employers response after the Constitutional Court ruling that various kinds. Therefore this study was conducted with normative research methods analytical descriptive with qualitative analysis using document study data collection tool to obtain the documents study secondary data sourced from primary legal materials, secondary and tertiary regarding layoffs Because Mistakes weight Settlement Following the Ruling of the Constitutional Court No. 012 / PUU-I / 2004.Keywords: Termination, serious mistakes, the Constitutional Court AbstrakBila pekerja melakukan kesalahan berat (tindak pidana) di tempat kerja sebagaimana ketentuan Pasal 158 UU Ketenagakerjaan No. 13/ 2003, maka dengan syarat-syarat tertentu (bukti: pekerja/buruh tertangkap tangan, ada pengakuan atau didukung oleh sekurang-kurangnya 2 orang saksi) pengusaha dapat melakukan PHK sepihak, tanpa melalui prosedur penetapan Pengadilan Hubungan Industrial. Mahkamah Konstitusi (MK) dengan Putusan Nomor 012/PUU-I/2003 telah menyatakan bahwa Pasal 158 UUK, tidak mempunyai kekuatan Hukum mengikat karena dinilai bertentangan dengan Pasal 27 ayat (1) Undang-Undang Dasar 1945. Pasca Putusan MK, Pengusaha tidak bisa melakukan PHK sebelum adanya putusan pengadilan umum yang berkekuatan hukum tetap (inkracht). Respon Pengusaha pasca Putusan MK tersebut bermacam macam. Untuk itu penelitian ini dilakukan dengan metode penelitian normatif yang bersifat deskriptif analistis dengan analisis kualitatif dengan menggunakan alat pengumpul data studi dokumen untuk memperoleh data sekunder yang bersumber dari bahan hukum primer, sekunder dan tersier mengenai Penyelesaian PHK Karena Kesalahan Berat Pasca Putusan Mahkamah Konstitusi No. 012/PUU-I/2004. Kata Kunci : Pemutusan Hubungan Kerja, Kesalahan Berat, Putusan MK